The Primitivist Imaginary in Iberian and Transatlantic Modernisms - Cunha Leal, Joana; Pinto dos Santos, Mariana (Routledge Research in Art History, 2024)
Taking into account politics, history, and aesthetics, this edited volume explores the main expressions of primitivism in Iberian and Transatlantic modernisms. Ten case studies are thoroughly analyzed concerning both the circulations and exchanges connecting the Iberian and Latin American artistic and literary milieus with each other and with the Parisian circles. Chapters also examine the patterns and paradoxes associated with the manifestations of primitivism, including their local implications and cosmopolitan drive. This book opens up and deepens the discussion of the ties that Spain and Portugal maintained with their imperial pasts, which extended into European twentieth-century colonialism, as well as the nationalist and folk aesthetics promoted by the cultural industry of Iberian dictatorships. The book significantly rethinks long-established ideas about modern art and the production of primitivist imagery. The book will be of interest to scholars working in art history, Iberian studies, Latin American studies, colonialism, and modernism. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.